MEDIA SCRAPBOOK DALAM MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR KOTA BENGKULU - Abdul Muktadir; Prayuningtyas Angger Wardhani; Alrahmat Arif; Jatu Wahyu Wicaksono (Jurnal Pendidikan Dasar, 2020)
Scrapbook Media Development in Increasing the Creativity of Elementary School Students in Bengkulu City. The purpose of this research is to develop a valid media scrapbook in increasing the creativity of fourth-grade students in elementary schools in Bengkulu. The method used is Research and Development by using the ADDIE model ((Analysis - Design - Develop - Implement - Evaluate). The target of this study is early grade elementary school students. The results showed that the scrapbook media validation of material experts that had been done obtained average scores. -The average is 4.75 in the very good category and suitable for use. Language validation also obtained a score of 4.62 in the good category and suitable for use. Based on these results it can be concluded that the scrapbook media that has been developed is suitable to be used to increase the creativity of elementary school students.